Ovid, Metamorphoses, 3.511-733 : Latin text with introduction, commentary, glossary of terms, vocabulary aid and study questions /: Latin text with introduction, commentary, glossary of terms, vocabulary aid and study questions. Liber 3, lines 511-733 (2016) - Ovid, 43 B.C.-17 A.D. or 18 A.D
No abstract available